2022
DOI: 10.3390/cells11030388
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Bone Metastasis: A Narrative Review of Emerging Targeted Drug Delivery Systems

Abstract: Bone is one of the most common metastatic sites among breast cancer (BC) patients. Once bone metastasis is developed, patients’ survival and quality of life will be significantly declined. At present, there are limited therapeutic options for BC patients with bone metastasis. Different nanotechnology-based delivery systems have been developed aiming to specifically deliver the therapeutic agents to the bone. The conjugation of targeting agents to nanoparticles can enhance the selective delivery of various payl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Treatment options for BC bone metastasis is hindered by the complex bone microstructure and a lack of an EPR effect due to low blood flow ( 56 ). Hence, non-targeted liposomes/LNP may have limited accumulation in the bones due to their size and low penetrability of the bone ( 71 ). Active targeting strategies could be taken into consideration when using liposomes/LNP to treat bone metastasis, including targeting both the tumor microenvironment and cancer cells simultaneously.…”
Section: Metastatic Breast Cancer Treatments Via L...mentioning
confidence: 99%
“…Treatment options for BC bone metastasis is hindered by the complex bone microstructure and a lack of an EPR effect due to low blood flow ( 56 ). Hence, non-targeted liposomes/LNP may have limited accumulation in the bones due to their size and low penetrability of the bone ( 71 ). Active targeting strategies could be taken into consideration when using liposomes/LNP to treat bone metastasis, including targeting both the tumor microenvironment and cancer cells simultaneously.…”
Section: Metastatic Breast Cancer Treatments Via L...mentioning
confidence: 99%
“…Previous studies have demonstrated that about 0.16 million patients were affected by BC in the United States in 2017 ( Torre et al, 2016 ; Li et al, 2020a ). Since 2020, there have been 2.3 million new cases of BC worldwide every year, and the total number of BC patients is predicted to increase by 50% by 2040 ( Dias et al, 2021 ; Shao and Varamini, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Report of the American Cancer Society, BC is second only to lung cancer in the number of cancer-related deaths among women. In recent years, the incidence of BC has been increasing at an annual rate of approximately 0.3%, with 2.3 million new cases worldwide in 2020 and a significant increase in mortality from 1990 to 2015 (3,4). According to Surveillance, Epidemiology and End Results (SEER) data, the 5-year survival rate of patients with stage IIIA and stage IIIB BC was 52% and 48%, respectively, and the median survival of patients with stage III BC was 4.9 years (2,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%